Systematic Literature Review: Jenis Kesalahan Mahasiswa atau Peserta Didik pada Pembuktian Matematis - Cici Wulandari Sitorus; Rusi Ulfa Hasanah; Syifa Husna Ramadhani (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Mathematical proof is a series of logical statements, where one statement implies another, which will provide an explanation of the truth of a statement. In mathematical proof, there are several mistakes that students or students often make when solving problems. The aim of this research is to find out the types of students’ or students’ errors in mathematical proof. This research is a systematic review research, which was carried out by comparing and analyzing articles taken from digital databases such as Springer Link and Semanthic Schoolar. Articles that have been searched for with specified keywords are then excluded according to the specified parameters, so that several reference articles are obtained. The research results show that the types of students’ or students’ errors in mathematical proof are as follows: (1) Conceptual errors with indicators, namely errors in understanding and recognizing commands or symbols in the problem. (2) Principle errors with indicators, namely errors in determining the problem solving strategy or theorem in the problem. (3) Operational errors with indicators, namely errors in algebra operations and problem solving procedures as well as errors in completing proofs correctly.